The Root canal treatment from patients’ perspective: knowledge, awareness, and expectations: Awareness of patients’ on Root Canal Treatment - Qasim, Muhammad; Anjum, Omair; Das, Gotam; Naz, Fariha; Khan, Saima Razaq; Ahmed, Abdul Razzaq; Chaturvedi, Saurabh (Vojnosanitetski pregled, 2022)
Background/Aim. Root canal treatment (RCT) is one of the most common endodontic procedures for which patients visit the dentist. Patient’s knowledge, awareness, and attitude regarding root canal treatment are an interesting problem in everyday dentistry. Therefore, the study aimed to evaluate the knowledge, awareness, and attitude of patients coming for endodontic treatment. Methods. Questionnaire surveys were carried out in a group of 209 patients, including queries characterizing their knowledge, awareness, and attitude towards the RCT – their experiences, expectations, potential problems, and management expenses. Results. Exploring the knowledge of individuals concerning RCT, it was noticed that 51% of the surveyed patients in the past had experienced endodontics treatment. Fifty-two percent of participants reported that they knew the charges of the RCT, and 50% of them said that the price was sufficient for the difficulty of the process. The study confirmed that 47% of the participants still prefer specialists to perform the RCT. Conclusion. An enhancement of knowledge and awareness of people about the RCT has been observed, as well as a need of providing more information to patients about endodontics and the benefits of saving teeth.